Utilisation of wood biomass residues from fruit tree branches, evergreen hardwood shrubs and Greek fir wood as raw materials for particleboard production. Part A. Mechanical properties - Lykidis, Charalampos; Grigoriou, Athanasios; Barboutis, Ioannis (Wood Material Science & Engineering, 2014)
Abstract This paper investigates the potential of utilising wood biomass from fruit tree branches and evergreen hardwood shrubs as raw materials in the production of particleboards when mixed with Greek fir wood particles. The main mechanical properties of the boards made therefrom were determined and compared with those made of typical industrial wood (IW) particles. The highest modulus of rupture and elasticity (30.0 N/mm2 and 4330 N/mm2, respectively) in bending and screw withdrawal (SW) resistance (127.8 N/mm) were reported for boards made of Greek fir and were downgraded when the fruit tree branches or evergreen hardwood shrub particles also participated. The participation of fruit tree branch particles in proportions higher than 50% improved the internal bond (IB) of fir produced boards, while the highest IB strength (0.95 N/mm2) was reported for boards made of fruit tree branches. Particleboards made of evergreen hardwood shrubs showed inferior mechanical properties compared with those made of IW particles. The latter also showed superior bending strength but inferior SW resistance compared with boards made of fruit tree branches. Hygroscopic and other properties are under determination and will be presented and discussed in the second part of the work.
doi: 10.1080/17480272.2013.875589
Keywords: evergreen hardwood shrubs; fruit tree branches; Greek fir; mechanical properties; particleboard